Design of wlan band notched uwb monopole antenna with stepped geometry using modified EBG structure - Pandey G.K.; Singh H.S.; Bharti P.K.; Meshram M.K. (My University, 2025)
A WLAN band notched compact ultra-wideband (UWB) microstrip monopole antenna with stepped geometry is proposed. A L-slot loaded modified mushroom type Electromagnetic Band Gap (EBG) is designed, analyzed and used to realize notched band characteristics for wireless local area network (WLAN) in the UWB frequency range. The proposed antenna having partial ground plane is fabricated on a low cost FR4 substrate having dimensions 40 (Lsub) × 30 (Wsub) × 1:6 (h)mm3 and is fed by a 50ωmicrostrip line. The results show that the proposed antenna achieves impedance bandwidth (VSWR < 2) from 2.3 GHz to 11.4 GHz with band notched characteristics (VSWR > 2) from 4.9 GHz to 6 GHz. Fidelity factor for proposed antenna is also analyzed to characterize time domain behavior. Simulation and measurement results of VSWR are found in good agreement.